The Swimming Drill Book - Guzman, Ruben J., 1957- (Human Kinetics, 2017)
Technique is critical in swimming performance. In the pool or open water, coaches and athletes alike know that efficiency in entering the water and in moving through it equates to milliseconds of improvement—milliseconds that make all the difference in a competition. That’s where The Swimming Drill Book continues to deliver. The first edition quickly became the best-selling drill book in the sport. Now, this second edition ups the ante with more drills, new variations, and expanded coverage to help every swimmer.